Exequatur of Sharia Economic Sector Arbitration Awards in The National Legal System - Jalaludin, Diding (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2023)
Exequatur is the act of the Chief Justice of the Supreme Court granting an executive title to an arbitral award, allowing it to be enforced with the assistance of state instruments if required. This exequatur can take the form of either a stamp affixed to the arbitral award or a separate determination (aparte beschikking). The objective of this research is to identify the judicial bodies that hold the competence to grant exequatur for arbitral awards in Sharia economics and business. The study employs a normative legal approach, concentrating on norms derived from applicable legislations and regulations. Currently, the arbitration settlement cases in the Islamic economics field are handled by two courts. The Sharia exequatur arbitral award is governed by Article 59, paragraph (1) of Law Number 30 of 1999 on Arbitration and ADR. The District Court is authorized to execute this award while the Religious Courts are given the authority to execute and annul Sharia arbitration decisions, according to Supreme Court Regulation (PERMA) Number 14 of 2016 regarding Procedures for the Settlement of Sharia Economic Cases. The Arbitration Law and ADR need expeditious revision to incorporate the existence of Sharia arbitration, including the unification of all authority relating to sharia arbitration given to 1 (one) judicial environment, namely the Religious Courts. Exequatur adalah tindakan Ketua Pengadilan yang memberikan executoriale titel pada putusan arbitrase, yang memungkinkan putusan arbitrase untuk dilaksanakan eksekusi dengan bantuan instrumen negara jika diperlukan. Exequatur ini dapat berupa stempel yang ditempelkan pada putusan arbitrase atau penetapan terpisah (aparte beschikking). Tujuan dari penelitian ini adalah untuk mengidentifikasi badan-badan peradilan yang memiliki kompetensi untuk memberikan exequatur untuk putusan arbitrase dalam ekonomi dan bisnis Syariah. Penelitian ini menggunakan pendekatan hukum normatif, yang berkonsentrasi pada norma-norma yang berasal dari peraturan perundang-undangan yang berlaku. Saat ini, kasus-kasus penyelesaian arbitrase di bidang ekonomi syariah ditangani oleh dua pengadilan. Exequatur putusan arbitrase syariah diatur dalam Pasal 59 ayat (1) UU No. 30 Tahun 1999 tentang Arbitrase dan APS. Pengadilan Negeri berwenang untuk mengeksekusi putusan ini, sedangkan Pengadilan Agama diberikan kewenangan untuk mengeksekusi dan membatalkan putusan arbitrase Syariah, sesuai dengan Peraturan Mahkamah Agung (PERMA) Nomor 14 Tahun 2016 tentang Tata Cara Penyelesaian Perkara Ekonomi Syariah. UU Arbitrase dan APS perlu segera direvisi untuk memasukkan keberadaan arbitrase Syariah, mencakup penyatuan seluruh kewenangan yang berkaitan dengan arbitrase syariah diberikan pada 1 (satu) lingkungan peradilan, yaitu Pengadilan Agama.